(untitled) (InKoj. Philosophy & Artificial Languages, New series, 2010)
ABSTRACT The text is a revised version of a public lecture delivered in Parma, Italy, on February 9, 2010. It outlines a definition of linguistic ecology and analyzes the role of the formal education system in the linguistic ecology of modernity. The shift from solid to liquid modernity is shown to have farreaching implications for schools and for languages that in turn are bound up with the ecological health of the planet. I argue that interlinguistics can yield important insights into the linguistic ecology of transmodernity, a systemic alternative to the present sociological impasse. RESUMO La teksto estas reviziita versio de publika prelego prezentita en Parma, Italio, la 9an de februaro, 2010. Ĝi skizas difinon de lingva ekologio kaj analizas la rolon de la formala eduksistemo en la lingva ekologio de la moderneco. Montriĝas ke la transiro de solida al likva moderneco kuntrenas profundajn sekvojn por la lernejoj kaj la lingvoj, kaj ke ĉio ĉi kunplektiĝas kun la ekologia sano de la planedo. Mi argumentas, ke la interlingvistiko povas grave kontribui al nia kompreno pri la lingva ekologio de la transmoderneco, konceptita kiel sistema alternativo al la nuna sociologia sakstrato.